2014
DOI: 10.1016/j.mib.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Variability of chromosome structure in pathogenic fungi—of ‘ends and odds’

Abstract: Chromatin structure can affect the organization and maintenance of chromosomes. Recent discoveries in several filamentous fungi suggest mechanisms for the clustering and co-regulation of secondary metabolite genes or pathogenicity islands. An extreme case of this may be fungal “accessory”, “conditionally dispensable”, or “supernumerary” chromosomes that often confer beneficial traits. Fungal supernumerary chromosomes may be derived by similar mechanisms as animal or plant B chromosomes, and we thus propose tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 52 publications
3
74
0
Order By: Relevance
“…Matching the finding of few active genes, cytological data from plants and animals suggest that B chromosomes are heterochromatic, and most studies suggest that they are enriched for H3K9me2/3 [230, 231]. In fungi the hallmark chromatin feature of accessory chromosomes is H3K27me3 [22, 62, 145, 146], though transposable elements are still covered by H3K9me3 in Fusarium and Z. tritici (Figure 5). Thus, the separating characteristic –at least for now– seems to be the presence of H3K27me3 and facultative heterochromatin on accessory chromosomes.…”
Section: Not All Chromosomes Are Equalmentioning
confidence: 83%
See 1 more Smart Citation
“…Matching the finding of few active genes, cytological data from plants and animals suggest that B chromosomes are heterochromatic, and most studies suggest that they are enriched for H3K9me2/3 [230, 231]. In fungi the hallmark chromatin feature of accessory chromosomes is H3K27me3 [22, 62, 145, 146], though transposable elements are still covered by H3K9me3 in Fusarium and Z. tritici (Figure 5). Thus, the separating characteristic –at least for now– seems to be the presence of H3K27me3 and facultative heterochromatin on accessory chromosomes.…”
Section: Not All Chromosomes Are Equalmentioning
confidence: 83%
“…In F. fujikuroi deletion of kmt6 is lethal, and effects of derepression of secondary metabolite gene clusters were studied by RNAi-mediated downregulation of kmt6 [146]. Again, H3K27me3 covers almost a third of the whole genome, including almost all of the smaller chromosomes (Figure 5C), the so-called “accessory” chromosomes [22]. In E. festucae , H3K9me3 and H3K27me3 in combination were reduced in secondary metabolite gene clusters that produce lolitrems and ergot alkaloids when the fungus was growing in planta [147].…”
Section: Chromosome Landmarks: Origins Telomeres and Centromeresmentioning
confidence: 99%
“…Genome-wide studies in several fungi aiming to study chromatin revealed that TE-rich regions are generally associated to highly condensed chromatin that restricts transcription and TE activity (Lewis et al 2009;Connolly et al 2013;Galazka and Freitag 2014). Therefore, TEs can influence the expression of neighboring genes such as effectors, as they can direct the formation of heterochromatic regions (Lewis et al 2009).…”
mentioning
confidence: 99%
“…Extensive structural variation often occurs in these fast-evolving regions, leading to translocation, duplication, or loss of genetic material [1,4,5]. The highly dynamic regions can either be embedded within the core chromosomes or be located on separate chromosomes that often display presence/absence variations within a population, known as conditionally dispensable or accessory chromosomes [4,6]. The common occurrence of these bipartite genomes led to the “two-speed” model for pathogen genome evolution [4], suggesting that specific regions form sites of rapid genomic diversification to facilitate coevolution during host interactions [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the majority of the detected structural variations colocalize with these heterochromatic regions (Fig 1C–1E). This suggests a further link between chromatin and genome structure, and despite the general thought that heterochromatin suppresses genomic variation, heterochromatic regions appear highly variable in the plant pathogenic fungi analyzed to date (see [6] for additional examples).…”
Section: Introductionmentioning
confidence: 99%